The Malleability of the Past: "Íslendingabók" as Narrative History - Martina Ceolin (D.S. Brewer, 2022)
"Íslendingabók" (Book of Icelanders) is the earliest surviving history of Iceland, written by the priest Ari Þorgilsson sometime between 1122 and 1133. Despite spanning the period from the Settlement in the ninth century to 1118, the work is concise, which suggests that a specific selection of information was made by the author during the composition process. This hypothesis is supported by the quality of the information conveyed, which seems to favour Ari himself and his patrons, and by Ari’s omission of material that would compromise his view, evidence of which is nevertheless present in other sources. This article explores "Íslendingabók" as a careful reconstruction of the Icelandic past, thus as narrative history; the focus will be on the strategies and aims that lay behind the author’s project, not least on the ideological foundations that shaped Ari’s views. This approach will allow for a better appreciation of the text and its production context, as compared to the influential but often uncritical methods used to study the work that flourished during the late nineteenth and early twentieth centuries and which still reverberate today, within both scholarly discussions of the work and popular contemporary attitudes in Iceland towards the country’s medieval history and culture.